Pengaruh Penggunaan Model Contextual Teaching & Learning (Ctl) Terhadap Hasil Belajar Seni Tari Di SMPN 1 Luhak Nan Duo - Ade Sofyanri; Fuji Astuti (FBS Universitas Negeri Padang, 2020)
This class action research aims to increase the activity of student learning outcomes in cultural art (dance) at class VII in SMP N 1 Luhak Nan Duo. This research was a quantitative research with using experimental method. This study used data that were derived from the results of cultural art learning of students class VII at SMPN 1 Luhak Nan Duo or learning outcomes after the experiments were carried out. Techniques of data collection used in this study were tests given at the end of the cycle. Data collection were done by taking observation, tests and documentation. Meanwhile, technique of data analysis in quantitative research used statistics. The results of the study show that there is an effect of the student learning outcomes using learning model (CTL) on dance motion material based on time and energy, rather than the student learning outcomes that is taught with an experimental class average only gets 78.2 and 71.3 for the value of the control class.